PENGARUH EKSTRAKURIKULER SENI TARI TERHADAP PEMBENTUKAN KARAKTER KREATIF SISWA SMA NEGERI 4 PEKANBARU - Da’iyah, Nadhrah ’Uqty Da’iyah Uqty; ', Hambali; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This event will be based on research by the existence of extracurricular activities dance in SMA Negeri 4 Pekanbaru. Extracurricular dance art is an activity that is implemented outside of school lessons and is associated with beauty and rhythmic body movements followed by a resounding – sounds or music. Extracurricular dance is also a means for the development of creativity against the interest, talent and potential that exist in the student., therefore one establishment of creative character in the scope of the school's extracurricular program is art, especially the art of dance. Hence the formulation of the problem of the research is